Compounds with distinct targets present diverse antimicrobial and antibiofilm efficacy against candida albicans and streptococcus mutans, and combinations of compounds potentiate their effect - Lobo, Carmélia Isabel Vitorino [UNESP]; Lopes, Ana Carolina Urbano de Araújo [UNESP]; Klein, Marlise Inêz [UNESP] (MDPI, 2021)
Candida albicans and Streptococcus mutans interact synergistically in biofilms associated with a severe form of dental caries. Their synergism is driven by dietary sucrose. Thus, it is necessary to devise strategies to hinder the development of those biofilms and prevent cavities. Six compounds [tt-farnesol (sesquiterpene alcohol that decreases the bacterium acidogenicity and aciduricity and a quorum sensing fungal molecule), myricetin (flavonoid that interferes with S. mutans exopolysaccharides production), two 2’-hydroxychalcones and 4’-hydroxychalcone (intermediate metabolites for flavonoids), compound 1771 (inhibitor of lipoteichoic synthase in Gram-positive bacteria)] with targets in both fungus and bacterium and their products were investigated for their antimicrobial and antibiofilm activities against single-species cultures. The compounds and concentrations effective on single-species biofilms were tested alone and combined with or without fluoride to control initial and pre-formed dual-species biofilms. All the selected treatments eliminated both species on initial biofilms. In contrast, some combinations eliminated the bacterium and others the fungus in pre-formed biofilms. The combinations 4’-hydroxychalcone+tt-farnesol+myricetin, 4’-hydroxychalcone+tt-farnesol+fluoride, and all compounds together with fluoride were effective against both species in pre-formed biofilms. Therefore, combinations of compounds with distinct targets can prevent C. albicans and S. mutans dual-species biofilm build-up in vitro.
Keywords: Antibiofilm agents; Antimicrobial agents; Biofilm; Candida albicans; Extracellular matrix; Streptococcus mutans